The socio-economic impact assessment of biofuels production in South Africa: A rapid structured review of literature. Issue 1 (31st December 2023) - L.M., Mvelase; S.R.D, Ferrer; N, Mustapha
Abstract: Biofuels as a substitute for conventional aviation and motor vehicle fuels have received considerable global interest over the past decades mainly due to their perceived economic, social, and environmental benefits. Despite these economic benefits, most developing countries, including South Africa (SA), have yet to produce commercial biofuels. This study aims to inform South African policymakers. Prospective producers of biofuels about the potential socio-economic returns from producing biofuels at a commercial level through a structured rapid review of the literature differs from the peer-reviewed studies to date in South Africa, which focussed more on assessing the economic viability and environmental impacts of biofuels production. The systematic review methodology was used. About 48% of the published empirical studies reviewed integrated the socio-economic and environmental impact assessment, followed by studies that only examined the social impacts of biofuel (about 26%), about 15% of the studies examined economic impact only, and 11.54% examined the socio-economic impact. The results revealed that although the production of biofuels is associated with a positive socio-economic benefit, the biofuel industry is not viable without government support and the selling price of biofuel is not competitive relative to gasoline and petroleum alternatives. Lastly, the results revealed a need for more objective empirical studies in South Africa that can quantify the economy-wide implications of biofuels (especially second-generation biofuels) production. Only two ( n = 2) of the 28 reviewed studies were conducted in South Africa from 28 studies reviewed. Both studies conducted in South Africa were feasibility studies focusing more on bioethanol; no study quantified the economy-wide impacts. The study recommends the implementation of the biofuels support mechanism by the government. Furthermore, amendments to the existing biofuels regulatory framework are recommended in order to support the production of advanced biofuels.